Effects of cymbopogon citratus extract on quality of chevon patties during storage (2017)
Lipid oxidation and growth of undesirable microorganisms in meat and meat products render them unacceptable for human consumption. A need therefore arises to explore the use of natural antioxidants and antimicrobials to prevent deterioration as synthetic ones have been found to pose high health risks to consumers. The effect of Lemon grass (Cymbopogon citratus) extract (LGE) on shelf stability of cooked Chevon patties during refrigerated storage was investigated. The experiment was a factorial experiment in a completely randomized design with five antioxidant treatments (Treatment A (0.2% Vit E), B (control), C (0.1% LGE), D (0.2% LGE), E (0.3% LGE) and four storage days (0, 3, 6, 9). Proximate composition of patties were determined using standard method, sensory qualities were evaluated using a 9-point hedonic scale, lipid oxidation was monitored by malondialdehyde formation with 2-thiobarbituric acid (TBARS) assay. Nutrient composition of patties at all treatment levels, except ash were affected (p<0.05) by the antioxidant treatments. Lipid oxidation rates of patties and pH were reduced (p<0.05) by antioxidant treatments during storage. Total Plate Count (TPC) was also (p<0.05) reduced and all counts were below 7logCFU/g, the Maximum Permissible Limit (MPL) for TPC. Sensory qualities were not (p<0.05) influenced by the antioxidant treatments however, a high Overall Acceptability score (6.70+1.16) was observed for treatment D, closely followed by treatment A (6.60+0.97). Lemon grass extract at 0.2% level of inclusion had comparable effects with alplia-tocopherol in most parameters measured and can successfully replace its use at this level to improve the shelf-life of Chevon patties and also provide a meat product with natural additives.